Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.7759/cureus.26279
|View full text |Cite
|
Sign up to set email alerts
|

Service-Learning Programs and Projects for Medical Students Engaged With the Community

Abstract: The medical school curriculum has changed from using the term "pedagogy" to framing adult learning theories with the goal of applying knowledge to a clinical situation or real-life experiences. Service-learning programs (SLPs) in medical schools illustrate one of several adult learning principles and practices now used in today's curriculum that better prepare medical students for working with a variety of patients. ObjectiveThe researchers' aim was to assess medical students' learning experiences while partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…We found five overarching themes that intersect and/or compile the experiences of the learners while carrying out their GHCSL placements—these themes are to represent the preliminary findings of this pilot program at the Schulich School of Dentistry, Western University. Similar to other studies, the results of this study demonstrated positive findings and skills building in cultural humility, understanding of social determinants of health, and positive attitudes towards service-learning among dental learners [ 39 , 40 ]. The benefits of GHCSL for local communities were also optimized through the fostering of bidirectional participatory relationships and local capacity building.…”
Section: Discussionsupporting
confidence: 88%
“…We found five overarching themes that intersect and/or compile the experiences of the learners while carrying out their GHCSL placements—these themes are to represent the preliminary findings of this pilot program at the Schulich School of Dentistry, Western University. Similar to other studies, the results of this study demonstrated positive findings and skills building in cultural humility, understanding of social determinants of health, and positive attitudes towards service-learning among dental learners [ 39 , 40 ]. The benefits of GHCSL for local communities were also optimized through the fostering of bidirectional participatory relationships and local capacity building.…”
Section: Discussionsupporting
confidence: 88%